The merry viscount - MacKenzie, Sally (MacKenzie, Sally. Widow's brew series., 2019)
"The "fallen" ladies of Puddledon Manor's Benevolent Home are determined to rise above scandal--and forge a sparkling new future operating their own brewery and alehouse..."--Page 4 of cover.